OPTIMIZATION OF COMPOSITION AND FORMATION OF TITANIA SOL-GEL COATINGS ON TITANIUM SUBSTRATE USING DIP-COATING TECHNIQUE - Kristyna Svagrova (Ceramics-Silikáty, 2019)

(untitled)
The objective of this work was to use a sol-gel method to prepare bioactive coatings containing calcium and phosphate ions under various coating conditions on a non-porous titanium substrate. Titania sol based on tetra-n-butyl-orthotitanate was prepared by direct dissolution of reagents and from stock ethanol solutions. The titanium substrate was grinded and coatings were prepared on the surface using a dip-coating technique under different coating conditions which are critical for preparation of sol-gel coatings. The conditions, which included the coating speed, chosen reagents and other experimental conditions, were selected based on previous experiments. The coating process was followed by drying for various periods of time and firing of the coated substrates. Bioactivity of the fired coatings was tested with a static in vitro test in simulated body fluid. After the firing and after the in vitro test the coatings were characterized with an optical microscope and with a scanning electron microscope. After the firing all types of coatings were made up of white circle areas of diverse morphology. After the in vitro test all types of the coatings contained a new Ca-P nuclei and white Ca-P phases of diverse morphology and size. The most continual precipitated Ca-P phases were detected on a sample prepared at the dipping and withdrawal speed of 20 cm.min-1 with the dwell time of 30 s.